1997
DOI: 10.1111/1523-1747.ep12336235
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning of the 210-kDa Paraneoplastic Pemphigus Antigen Reveals that Envoplakin Is a Component of the Antigen Complex

Abstract: Although the 210 and 190-kDa proteins are the most frequently detected antigens reacting with sera of patients with paraneoplastic pemphigus (PNP) in immunoblot analysis, there is still uncertainty as to the nature of these PNP antigens. To isolate and characterize a cDNA clone encoding the 210-kDa PNP antigen, we screened a human keratinocyte lambda gt 11 cDNA expression library by the immunoperoxidase method with serum IgG from a PNP patient. The IgG used for the immunoscreening of a keratinocyte cDNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 18 publications
5
65
0
2
Order By: Relevance
“…This further supports the previous result by Kim et al that immunoscreening a keratinocyte cDNA library with a PNP serum cloned a partial cDNA corresponding to envoplakin [30]. Joly et al showed that PNP sera react with a 185 kDa protein that co-migrates with the protein detected by a human IgM monoclonal antibody F12 [33], which has been established from lymphocytes of a pemphigus vulgaris patient [34], and it will be interesting to determine whether F12 reacts with periplakin.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This further supports the previous result by Kim et al that immunoscreening a keratinocyte cDNA library with a PNP serum cloned a partial cDNA corresponding to envoplakin [30]. Joly et al showed that PNP sera react with a 185 kDa protein that co-migrates with the protein detected by a human IgM monoclonal antibody F12 [33], which has been established from lymphocytes of a pemphigus vulgaris patient [34], and it will be interesting to determine whether F12 reacts with periplakin.…”
Section: Introductionsupporting
confidence: 86%
“…In fact, Kim et al (1997) have recently reported that by immunoscreening a keratinocyte cDNA library with a PNP serum they cloned a partial cDNA conesponding to envoplakin, which strongly suggests that the 210 kDa protein is envoplakin [30]. In the present study, using polyclonal antibodies specific to envoplakin and periplakin and sera of Immunoblot analysis…”
Section: Introductionsupporting
confidence: 52%
“…The 210-kD antigen recognized by immunoprecipitation was found to be a doublet, of which the slower migrating band was desmoplakin II. The faster migrating band, which is recognized by immunoblotting (8), was later identified by cDNA cloning as envoplakin (9). Envoplakin is a novel precursor protein of the cornified envelope that is homologous to desmoplakin (10).…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence reveals typical binding of both IgG and C3 in a focal, intercellular epidermal pattern and linear granular pattern at the basement membrane zone. Immunoprecipitation and immunoblotting reveal several characteristic target antigens of molecular weights 250, 230, 210, 190 and 170 kDa corresponding to desmoplakin, the 230-kDa bullous pemphigoid (BP) antigen BP230, envoplakin, periplakin and transmembrane protein [5][6][7][8][9]. In addition,a pathogenic role has also been suggested for antidesmoglein (Dsg) antibodies [10].…”
Section: Discussionmentioning
confidence: 99%